Analisis Peran Fasilitas Ruang Belajar dalam Mendukung Konsentrasi Belajar Siswa Di SD Negeri 8 Talang Kelapa - Dania Zalyyanti; Ade Akhmad Saputra; Zulkipli Zulkipli (JURNAL ILMIAH NUSANTARA, 2026)
Education serves as a fundamental instrument in the formation of personal integrity and human resource development, the success of which is significantly influenced by the interaction between students and their physical environment. Neurally, the learning process involves the formation of synaptic connections in the brain, requiring a distraction-free environment to ensure the optimal transformation of information into functional knowledge. This study aims to examine and analyze the role of learning space facilities on student concentration during the learning process at SD Negeri 8 Talang Kelapa. A qualitative approach with a case study method was employed to descriptively reveal the manifestation of student concentration behavior in relation to the physical condition of the classroom. Primary data sources involved classroom teachers, infrastructure staff, and students, while secondary sources included school inventory documents and literature related to environmental psychology in learning. Data collection techniques were conducted through non-participant observation over 10 meetings, structured and unstructured interviews, and documentation of learning space physical conditions. Data analysis was carried out systematically through the stages of data collection, data reduction, data display, and conclusion drawing based on the Miles & Huberman model (1994). The results indicate that learning space facilities including lighting, air circulation, and furniture layout play a crucial role as mechanical prerequisites for students to achieve maximum concentration. Conversely, limitations in physical facilities potentially hinder students' mental focus, resulting in a decline in the quality of subject matter comprehension. This research provides implications for the importance of sustainable infrastructure management to realize a conducive learning environment at the elementary school level.